Transfersomes: A Promising Nanoencapsulation Technique for Transdermal Drug Delivery - Shakthi Apsara Thejani Opatha; Varin Titapiwatanakun; Romchat Chutoprapat (MDPI AG, 2020)
Transdermal delivery systems have gained much interest in recent years owing to their advantages compared to conventional oral and parenteral delivery systems. They are noninvasive and self-administered delivery systems that can improve patient compliance and provide a controlled release of the therapeutic agents. The greatest challenge of transdermal delivery systems is the barrier function of the skin's outermost layer. Molecules with molecular weights greater than 500 Da and ionized compounds generally do not pass through the skin. Therefore, only a limited number of drugs are capable of being administered by this route. Encapsulating the drugs in transfersomes are one of the potential approaches to overcome this problem. They have a bilayered structure that facilitates the encapsulation of lipophilic and hydrophilic, as well as amphiphilic, drug with higher permeation efficiencies compared to conventional liposomes. Transfersomes are elastic in nature, which can deform and squeeze themselves as an intact vesicle through narrow pores that are significantly smaller than its size. This review aims to describe the concept of transfersomes, the mechanism of action, different methods of preparation and characterization and factors affecting the properties of transfersomes, along with their recent applications in the transdermal administration of drugs.